2014
DOI: 10.1103/physrevb.89.024413
|View full text |Cite
|
Sign up to set email alerts
|

Domain wall motion in junctions of thin-film magnets and topological insulators

Abstract: We derive the equations of motionof a domain wall in a thin-film magnet coupled to the surface states of a topological insulator, in the presence of both an electric field along the domain wall and a magnetic field perpendicular to the junction. We show how the electric field acts as a chirality stabilizer holding off the appearance of Walker breakdown and enhancing the terminal velocity of the wall. We also propose a mechanism to reverse the domain wall chirality in a controllable manner, by tuning the chiral… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 28 publications
0
35
1
Order By: Relevance
“…It was described in Ref. [55], where they made use of an electric field to tune the chirality through the mechanism explained above, while here we have shown that it can be done also by applying a gate voltage.…”
Section: A Equilibrium Configuration Of the Dwmentioning
confidence: 66%
See 1 more Smart Citation
“…It was described in Ref. [55], where they made use of an electric field to tune the chirality through the mechanism explained above, while here we have shown that it can be done also by applying a gate voltage.…”
Section: A Equilibrium Configuration Of the Dwmentioning
confidence: 66%
“…It was first suggested in Ref. [55], where an electric field was needed, and afterwards in Ref. [56], where it was shown that a similar effect could be achieved in equilibrium.…”
Section: B Current Induced Magnetization Dynamicsmentioning
confidence: 97%
“…A magnetic domain wall in proximity to the Dirac electron generates a chiral state, in analogy to the Jackiw-Rebbi zero mode 13 , which in turn alters its dynamics and stability [14][15][16][17] . One could thus expect more novel properties when the Dirac states of a TI couple to nontrivial spin textures, such as skyrmions 18,19 , which is the main issue of this work.…”
mentioning
confidence: 99%
“…It should be noted that, although their effect is negligible on the bulk propagation of light, the 1D Fermi arc chiral states at the edges of a WSM would give additional resonances as surface electromagnetic modes. However, the polarization tensor of 1D chiral electrons has already been computed in the literature 47,48 and therefore the Fermi arc contribution can be distinguished from bulk propagation.…”
Section: Discussion and Conclussionsmentioning
confidence: 99%